511 Organising A Surgical Conference During The COVID-19 Pandemic – Is It 'Virtually' The Same?. (12th October 2021) - Hashmi, Y; Sahu, M A; Hatt, K; Osman, S; Bhuiyan, Z A; Ahmed, U
Abstract: Introduction: Surgical conferences are invaluable events for healthcare professionals; they provide opportunities to engage with upcoming scientific discoveries, network professionally with peers as well as expand learning through lectures and workshops. For medical students, conferences provide an opportunity to expand understanding beyond the undergraduate curriculum in an interactive manner. COVID-19 has caused disruption to the organisation and attendance of in-person conferences (IPCs). Virtual conferences (VCs) offer a viable solution, allowing delegates to attend from the comfort of their own homes. Method: The aim of our study was to evaluate an organised VC and explore the perceived benefits and limitations of VCs compared to IPCs. A virtual one-day trauma & orthopaedics (T&O) conference was organised involving lectures, workshops, poster, and oral presentations. Anonymous questionnaire forms were distributed to delegates following the conference to assess the aims of our paper. Results: From 106 responses, 96.2% rated the conference as 'Excellent' or 'Good' with 92.5% stating that it increased their passion for T&O surgery. Based on a five-point Likert scale (5= strongly agree, 1= strongly disagree), mean score of agreement for preferring VCs to IPCs was 3.30(± 1.24). Key advantages of the VC were a lower cost (70.8%) and not having to travel (77.4%), whereas the main limitation was the inability to participate in hands-on workshops (84.9%). Conclusions: Despite the success of our VC, delegate feedback indicates a mixed response comparing VCs to IPCs. We share our findings to encourage similar events to be organised and for other specialties.